Financing Vaccine Equity : Funding for Day-Zero of the Next Pandemic - Agarwal, Ruchir; Reed, Tristan (World Bank, Washington, DC, 2022)
A lack of timely financing for purchases of vaccines and other health products impeded the global response to the COVID-19 pandemic. Based on analysis of contract signature and delivery dates in COVID-19 vaccine advance purchase agreements, this paper finds that 60–75 percent of the delay in vaccine deliveries to low- and middle-income countries is attributable to their signing purchase agreements later than high-income countries, which placed them further behind in the delivery line. A pandemic Advance Commitment Facility with access to a credit line on day-zero of the next pandemic could allow low- and middle-income countries to secure orders earlier, ensuring a much faster and equitable global response than during COVD-19. The paper outlines four options for a financier to absorb some or all of the risk associated with the credit line and discusses how the credit would complement other proposals to strengthen the financing architecture for pandemic preparedness, prevention, and response.